A Resource-Based View of Human Capital and Performance in Deposit-Taking Saccos in Kirinyaga County, Kenya - Murage, Nancy Waithira; Waithaka, Paul (European Scientific Journal, ESJ, 2025)
Deposit-taking savings and credit cooperative societies (SACCOs) in Kirinyaga County continue to grapple with challenges such as low profitability, high staff turnover, and limited technological adoption, factors that undermine their financial sustainability and operational efficiency. This study applies the Resource-Based View (RBV) to examine the relationship between human capital and the performance of these SACCOs. A descriptive research design was adopted, combining both qualitative and quantitative approaches. Data were collected using semi-structured questionnaires administered to SACCO managers and employees, alongside secondary data from financial reports. Ten SACCOs were purposively selected for analysis, and statistical techniques were employed to assess the influence of internal resources on performance outcomes. The findings indicate that while human capital, particularly well-trained and experienced staff, is recognized as a valuable resource, its practical impact on performance is often constrained by inconsistencies in human resource practices. The study concludes that strategic investment in human capital is essential but must be accompanied by coherent policies in recruitment, training, motivation, and performance management to yield sustainable benefits. By highlighting the centrality of human resources within the RBV framework, the study offers actionable insights for SACCOs seeking to enhance operational efficiency, strengthen competitive advantage, and contribute more effectively to regional economic development.